Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias – and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

Une lutte sans trêve - Davis, Angela (La Fabrique, 2016)
Quels sont les liens entre l’industrie militaro-carcérale américaine, l’apartheid en Israël-Palestine, les mobilisations de Ferguson, Tahrir et Taksim ? Qu’est-ce que l’expérience des Black Panthers et du féminisme noir nous dit des rapports actuels entre les oppressions spécifiques et l’impérialisme ? Témoin et actrice de luttes de libération pendant plus d’un demi siècle, Angela Davis s’exprime ici sur l’articulation de ces différents combats, pour une nouvelle génération saisie par l’urgence de la solidarité internationale.
https://www-cairn-info.proxy.bibliotheques.uqam.ca/une-lutte-sans-treve–9782358720809.htm
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; féminismes noirs; histoire et politique; intersectionnalité; inégalités; militance; pol4212; premier cycle; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Mobilisations féminines au Cameroun français dans les années 1940-1950: l’ordre du genre et l’ordre colonial fissurés - Ndengue, Rose (Le Mouvement Social, 2016)
Durant la décennie qui suit la Seconde Guerre mondiale, le Cameroun sous tutelle française, comme tous les territoires de l’Empire colonial français, connaît une effervescence sociale et politique. Celle-ci se traduit par des mobilisations de Camerounaises et une montée en puissance de revendications nationalistes, face à l’insuffisance des réformes politiques et sociales mises en place. Cet article examine la manière dont, en s’inscrivant dans un paysage politique majoritairement masculin, des Camerounaises essayent de faire entendre leur voix en s’organisant pour défendre leurs intérêts. L’analyse des ressorts sur lesquels reposent les mobilisations féminines au Cameroun, met en évidence la dualité qui régit la présence des femmes sur la scène publique dans le contexte colonial. Dans une certaine mesure, leur démarche se situe dans un prolongement de l’imaginaire social dominant, mettant en avant des valeurs domestiques pour justifier une intervention des femmes sur la scène politique. Mais les mobilisations féminines visent également la défense d’un agenda propre aux femmes, ainsi que l’émergence d’un nouvel imaginaire social régi par l’égalité des sexes.
Keywords: 1900-1999; 1940-1949; 1950-1959; afrique; afro-féminisme; approches et analyses; cameroun; cours; discipline; discours dominant; féminisme africain; histoire; histoire et politique; militance; pol4022; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques